Copolyester resin and method for producing same
A copolyester resin with biodegradable and non-biodegradable blocks in specific ratios addresses thermoformability and biodegradability issues, enabling high-temperature processing and effective environmental decomposition.
Patent Information
- Application Number
- JP2023571188
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-01-13
- Filing Date
- 2023-05-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-05-23
AI Technical Summary
Existing biodegradable copolyester resins face limitations in thermoformability and biodegradability due to their molecular weight dependence on seawater degradability, with close melting and thermal decomposition temperatures, and low polymerization temperatures hindering high molecular weight synthesis.
A copolyester resin is developed by combining biodegradable and non-biodegradable blocks in specific molar ratios, with biodegradable blocks derived from hydroxyalkanoic acids and dibasic acids, and non-biodegradable blocks derived from structures like butylene succinate or butylene adipate terephthalate, allowing for high-temperature polymerization and improved thermoformability.
The copolyester resin exhibits excellent thermoformability and biodegradability, decomposing into oligomers that can be metabolized by microorganisms, with biodegradation rates exceeding 15% in various environments, including seawater, freshwater, and soil.
Smart Images

Figure 0007605346000001 
Figure 0007605346000002 
Figure 0007605346000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolyester resin and a method for producing the same. [Background technology]
[0002] Many synthetic resins do not decompose easily in the natural environment. Therefore, the deterioration of the natural environment caused by synthetic resins has become a problem. For example, discarded synthetic resins become microplastics and pollute the marine environment.
[0003] In response to the social issue of environmental degradation caused by the mass disposal of synthetic resins, there is a growing demand for sustainable products (packaging materials, films, etc.) made from resins that are biodegradable in all environments (seawater, freshwater, soil, compost, etc.).
[0004] An example of a resin that is biodegradable in any environment is polyhydroxyalkanoate (PHA). PHA has attracted attention as an environmentally friendly resin, and is widely used, with a demand for further expansion of its application range.
[0005] However, PHA has a low thermoformability compared to general-purpose resins because its melting temperature and thermal decomposition temperature are close, and thermal decomposition progresses during processing. In addition, when synthesizing PHA from monomers by chemical polymerization, it is difficult to synthesize high molecular weight polymers because the upper limit of the polymerization temperature is low. Therefore, there is a demand for biodegradable resins that can be polymerized at relatively high temperatures similar to those of general-purpose resins and that can be thermoformed.
[0006] In order to solve the above problems, a technique has been reported in which a specific chemical structure is introduced into a polyester that exhibits biodegradability in a limited environment, thereby allowing the polyester to exhibit biodegradability in other environments as well. For example, Non-Patent Documents 1 and 2 report copolyester resins that have seawater degradability and thermal properties. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] Polymer Degradation and Stability, 181, (2020), 109353 [Non-Patent Document 2] Polymer Degradation and Stability, 184, (2021), 109467 Summary of the Invention [Problem to be solved by the invention]
[0008] However, since the copolyester resins disclosed in Non-Patent Documents 1 and 2 are triblock copolymers, the seawater biodegradability of the copolyester resin depends on the molecular weight of the polylactic acid portion, which is a non-seawater degradable portion. Therefore, there are restrictions on the molecular weight when designing the copolyester resin. In addition, further improvements in thermoformability and biodegradability are required.
[0009] Therefore, an object of the present invention is to provide a copolyester resin having excellent thermoformability and biodegradability, and a method for producing the same. [Means for solving the problem]
[0010] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved, and have completed the present invention having the following gist.
[0011] That is, the present invention includes the following aspects. [1] A copolyester resin comprising a biodegradable block (X), which is a structural unit that exhibits biodegradability, and a non-biodegradable block (Y), which is a structural unit that is non-biodegradable. [2] The copolyester resin according to [1], wherein a molar ratio (X / Y) of the biodegradable block (X) to the non-biodegradable block (Y) is 1 / 99 to 95 / 5. [3] The copolyester resin according to [1] or [2], wherein the biodegradable block (X) is derived from a structure in which a hydroxyalkanoic acid or a dibasic acid (Ia) is bound to a glycol (Ib), and is a biodegradable block (X) derived from a polymer (x) containing a biodegradable structural unit. [4] The copolyester resin according to any one of [1] to [3], wherein the non-biodegradable block (Y) is derived from a polymer (y) containing a structural unit having non-biodegradability. [5] The copolyester resin according to any one of [1] to [4], wherein the average sequence length of the biodegradable block (X) is greater than 1.2. [6] The copolyester resin according to any one of [3] to [5], wherein the hydroxyalkanoic acid is a structural unit derived from 6-hydroxyhexanoic acid or a structural unit derived from polycaprolactone. [7] The copolyester resin according to any one of [3] to [6], wherein the dibasic acid (Ia) is represented by formula (1) and the glycol (Ib) is represented by formula (2). [ka] Formula (1) (In formula (1), n represents an integer of 4 to 8.) [ka] Formula (2) In formula (2), A represents a carbon atom or an oxygen atom, R1 represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms or a hydroxyl group, and R2 represents a hydrogen atom or a hydroxyl group. l and m each independently represent an integer of 0 to 4, provided that l+m is 1 or greater. However, when A is an oxygen atom, there is no H bonded to R1 or A. Also, either R1 or R2 is a hydroxyl group, but both R1 and R2 are not hydroxyl groups. [8] The copolyester resin according to any one of [3] to [7], wherein the biodegradable structural unit in the polymer (x) is represented by the following formula (3A) or the following formula (3B): [ka] Formula (3A) [ka] Formula (3B) (In formula (3A) and formula (3B), R3 represents a hydrogen atom or a methyl group, l and m each independently represent an integer of 0 to 4, l+m being 1 or greater, and n represents an integer of 4 to 8.) [9] The copolyester resin according to any one of [3] to [8], wherein the dibasic acid (Ia) is at least one selected from the group consisting of adipic acid, azelaic acid, and sebacic acid.
[10] The copolyester resin according to any one of [3] to [9], wherein the glycol (Ib) is at least one selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol.
[11] The biodegradable constitutional unit in the polymer (x) is A structural unit derived from a structure in which ethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which diethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and adipic acid are bonded, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which diethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and sebacic acid are bonded, A structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol, diethylene glycol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, diethylene glycol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, and a structural unit derived from a structure in which ethylene glycol, 2-methyl-1,3-propanediol, adipic acid, and sebacic acid are bonded, The copolyester resin according to any one of [3] to
[10] , which is at least one selected from the group consisting of:
[12] The copolyester resin according to any one of [4] to
[11] , wherein the non-biodegradable structural unit in the polymer (y) is derived from butylene succinate or butylene adipate terephthalate.
[13] The non-biodegradable structural unit in the polymer (y) is The copolyester resin according to any one of [4] to
[12] , which is either a structural unit derived from a structure in which 1,4 butanediol and succinic acid are bonded together, or a structural unit derived from a structure in which 1,4 butanediol, adipic acid, and terephthalic acid are bonded together.
[14] The copolyester resin according to any one of [1] to
[13] , wherein the biodegradable block (X), which is a structural unit exhibiting biodegradability, contains a unit (A) and a unit (B), and the unit (A) and the unit (B) are any of the following (i) to (iii): (i) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3 propanediol, adipic acid, and 2-methyl-1,3 propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4 butanediol, adipic acid, and 1,4 butanediol are bonded"; or (ii) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3 propanediol, sebacic acid, and 2-methyl-1,3 propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4 butanediol, sebacic acid, and 1,4 butanediol are bonded", or (iii) The unit (A) is a triad unit derived from a "structure in which 3-methyl-1,5-pentanediol, adipic acid, and 3-methyl-1,5-pentanediol are bonded together," and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, adipic acid, and 1,4-butanediol are bonded together."
[15] The copolyester resin according to any one of [1] to
[14] , wherein the copolyester resin has a melting point (Tm) of 65° C. or higher.
[16] The copolyester resin according to any one of [1] to
[15] , which exhibits biodegradability in a seawater environment, a freshwater environment, a soil environment, and a compost environment.
[17] A method for producing a copolyester resin according to any one of [1] to
[16] , which comprises a combination of a biodegradable block (X) and a non-biodegradable block (Y), comprising: The biodegradable block (X) is a block derived from a polymer (x) containing a biodegradable structural unit, The non-biodegradable block (Y) is a block derived from a polymer (y) containing a non-biodegradable structural unit, a step of subjecting the polymer (x) and the polymer (y) to a transesterification reaction to obtain a block copolymer containing the biodegradable block (X) and the non-biodegradable block (Y); A method for producing a copolyester resin comprising the steps of:
[18] A resin composition comprising the copolyester resin according to any one of [1] to
[16] .
[19] A sheet or film made of the resin composition according to
[18] . Effect of the Invention
[0012] According to the present invention, it is possible to provide a copolyester resin having excellent thermoformability and biodegradability, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The copolyester resin of the present invention will be described in detail below. However, the following description of the constituent elements is merely an example of one embodiment of the present invention, and the present invention is not limited to these contents.
[0014] (Copolyester resin) The copolyester resin of the present invention is a resin obtained by combining a biodegradable block (X), which is a structural unit that exhibits biodegradability, and a non-biodegradable block (Y), which is a structural unit that has non-biodegradability.
[0015] A substance being "biodegradable" means that, for example, when released into the natural environment, the substance is decomposed into carbon dioxide and water by the action of microorganisms, etc. Examples of "environments" in which a substance can be decomposed include seawater environments, freshwater environments, soil environments, and compost. However, in the present invention, particular attention is paid to biodegradability in a seawater environment. In the present invention, the term "biodegradable" refers to a seawater decomposition rate of 15% or more. On the other hand, in the present invention, "non-biodegradable" means that the decomposition rate in seawater is less than 15%. In the present invention, the decomposition rate is specified as "seawater environment", but it does not exclude environments other than seawater environment. It is more preferable that the decomposition rate is 15% or more not only in the seawater environment but also in other environments such as freshwater environment, soil environment, or compost.
[0016] The copolyester resin of the present invention has excellent biodegradability and can be polymerized and thermoformed at a relatively high temperature similar to that of general-purpose resins. In other words, the copolyester resin of the present invention has excellent thermoformability and biodegradability. Furthermore, a sheet, film, etc. can be obtained by using a resin composition containing the copolyester resin.
[0017] An example of the presumed mechanism of action by which the excellent effects of thermoformability and biodegradability are remarkably obtained is shown below. In the copolyester resin of the present invention, a biodegradable block (X), which is a structural unit that exhibits biodegradability, and a non-biodegradable block (Y), which is a structural unit that has non-biodegradability, are combined. Cleavage of the block (X) proceeds due to enzymes in the environment. As a result, the copolyester resin becomes an oligomer that can be metabolized by microorganisms, and the entire copolyester resin is biodegraded. Furthermore, the copolyester resin of the present invention contains a block (Y) having a structural unit that exhibits non-biodegradability and has excellent thermoformability. As a result, the entire copolyester resin has excellent thermoformability. In addition to the above characteristics, the copolyester resin of the present invention contains multiple types of biodegradable structural units in a well-balanced manner in specific proportions, which ensures that there are many sites where the cleavage of biodegradable moieties by enzymes in the environment can proceed, leading to enhanced biodegradability of the entire copolyester resin. More specifically, for example, the copolyester resin of the present invention contains a block (X) derived from a polymer (x) having a structural unit exhibiting biodegradability, which is derived from a structure in which a hydroxyalkanoic acid or a dibasic acid (Ia) is bonded to a glycol (Ib). Cleavage of this block (X) proceeds due to enzymes in the environment. As a result, the copolyester resin becomes an oligomer that can be metabolized by microorganisms, and the entire copolyester resin is biodegraded. Furthermore, the copolyester resin of the present invention contains a block (Y) derived from a polymer (y) having a structural unit exhibiting non-biodegradability and excellent thermoformability. As a result, the entire copolyester resin has excellent thermoformability. Since the copolyester resin is formed by containing the biodegradable block (X) and the non-biodegradable block (Y) in a specific mixing ratio, the cleavage of the biodegradable block (X) present in a specific ratio progresses, and the copolyester resin becomes an oligomer that can be metabolized by microorganisms, and the entire copolyester resin is biodegraded. Furthermore, since the copolyester resin of the present invention contains the non-biodegradable block (Y) in a specific ratio, the entire copolyester resin has excellent thermoformability. Furthermore, when the biodegradable block (X) derived from polymer (x) is arranged in a copolyester resin with a specific average chain length, the biodegradable block (X) site having this specific average chain length is cleaved by enzymes in the environment, causing the copolyester resin to become an oligomer that can be metabolized by microorganisms, and the entire copolyester resin is biodegraded. Furthermore, since the copolyester resin of the present invention has the non-biodegradable block (Y) derived from polymer (y) containing a structural unit having non-biodegradability with excellent thermoformability arranged in a specific molar ratio, the entire copolyester resin has excellent thermoformability.
[0018] The components of the copolyester resin will be described below. The copolyester resin contains a biodegradable block (X) and a non-biodegradable block (Y), and more preferably contains an appropriate combination of the biodegradable block (X) and the non-biodegradable block (Y). In addition, the copolyester resin contains a biodegradable block (X) derived from a polymer (x) containing a biodegradable structural unit, and a non-biodegradable block (Y) derived from a polymer (y) containing a non-biodegradable structural unit. The polymer (x) is preferably a polymer that is derived from a structure in which a hydroxyalkanoic acid or a dibasic acid (Ia) is bonded with a glycol (Ib) and contains a biodegradable structural unit. On the other hand, polymer (y) is a polymer containing a non-biodegradable structural unit, and is preferably, for example, a polymer having a structural unit that is derived from a structure in which a dibasic acid and a glycol are bonded and that exhibits non-biodegradability.
[0019] <Polymer (x) containing a biodegradable structural unit> The polymer (x) contains at least one biodegradable structural unit. The biodegradable structural unit contained in the polymer (x) may be used alone or in combination of two or more kinds. The structural unit contained in the polymer (x) is preferably derived from a structure in which a hydroxyalkanoic acid or a dibasic acid (Ia) is bonded to a glycol (Ib).
[0020] Examples of the hydroxyalkanoic acid or dibasic acid (Ia) and glycol (Ib) used to form the polymer (x) include those shown below. The seawater decomposition rate of the structure obtained by binding varies depending on the combination of the types of hydroxyalkanoic acids and dibasic acids and the types of glycols. Therefore, in order to form a biodegradable polymer (x), it is advisable to appropriately select suitable types from the hydroxyalkanoic acids, dibasic acids, and glycols exemplified below so that the structure obtained by binding exhibits a seawater decomposition rate of 15% or more.
[0021] <<Hydroxyalkanoic acid>> Examples of hydroxyalkanoic acids include glycolic acid, 2-hydroxypropanoic acid (lactic acid), 3-hydroxypropanoic acid, 2-hydroxybutanoic acid (2-hydroxybutyric acid), 3-hydroxybutanoic acid, 4-hydroxybutanoic acid, 3-hydroxy-3-methyl-butanoic acid, 2-hydroxypentanoic acid (2-hydroxyvaleric acid), 3-hydroxypentanoic acid, 5-hydroxypentanoic acid, 2-hydroxy-2-methyl-pentanoic acid, 3-hydroxyhexanoic acid, 6-hydroxyhexanoic acid, 6-hydroxyheptanoic acid, 3-hydroxyheptanoic acid, 7-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 8-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 9-hydroxynonanoic acid, 3-hydroxydecanoic acid, and 10-hydroxydecanoic acid. 1-6 Hydroxy C, optionally having an alkyl group 2-15Examples of units include alkanoic acid, 12-hydroxystearic acid, and ricinoleic acid.
[0022] The hydroxyalkanoic acid unit may be a corresponding lactone unit. Examples of lactone units include β-propiolactone, β-dimethylpropiolactone, γ-butyrolactone, γ-dimethylbutyrolactone, δ-valerolactone, and di-C lactone other than ε-caprolactone. 1-12 C which may have an alkyl group 3-15 Examples of units include lactones.
[0023] These hydroxyalkanoic acid units and lactone units can be used alone or in combination of two or more. Among these hydroxyalkanoic acid units, from the viewpoint of biodegradability, hydroxyalkanoic acid units such as 3-hydroxypropanoic acid, 3-hydroxybutanoic acid, 4-hydroxybutanoic acid (4-hydroxybutyric acid), 3-hydroxyvaleric acid, 3-hydroxyhexanoic acid, 6-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, and 10-hydroxydecanoic acid are preferred. 3-10 Alkanoic acid units (hydroxy C other than 3-hydroxybutyric acid) 3-10 Alkanoic acid units) or the corresponding lactone units are preferred.
[0024] The hydroxyalkanoic acid is preferably a structural unit derived from 6-hydroxyhexanoic acid or a structural unit derived from polycaprolactone. Here, poly(caprolactone) is a polyester represented by the following formula (t).
[0025] [ka] (In formula (t), a represents a positive integer.)
[0026] Poly(caprolactone) is a ring-opening reaction product of ε-caprolactone. The building block of poly(caprolactone) is the building block (6HH-U) derived from 6-hydroxyhexanoic acid (6HH). The constitutional unit of poly(caprolactone) means one residue of 6-hydroxyhexanoic acid (6HH) in the copolyester, specifically, means a structure in which the hydrogen atom in the hydroxy group and the hydroxy residue in the carboxyl group of 6-hydroxyhexanoic acid (6HH) have been removed.
[0027] <<Dibasic acid>> The dibasic acid is not particularly limited, but examples thereof include non-aromatic dicarboxylic acids, aromatic dicarboxylic acids, dicarboxylic anhydrides, halides, and esters thereof.
[0028] <<<Non-aromatic dicarboxylic acids>>> Examples of non-aromatic dicarboxylic acids include aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, unsaturated bond-containing non-aromatic dicarboxylic acids, etc. The number of carbon atoms in the non-aromatic dicarboxylic acid is not particularly limited, but is, for example, 3 to 15 carbon atoms.
[0029] Examples of the aliphatic dicarboxylic acid include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelabaidic acid, sebacic acid, and dodecanedicarboxylic acid. Examples of the alicyclic dicarboxylic acid include alicyclic dicarboxylic acids having 8 to 15 carbon atoms. Examples of alicyclic dicarboxylic acids include 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid. Examples of the unsaturated bond-containing non-aromatic dicarboxylic acid include maleic acid and fumaric acid.
[0030] <<<Aromatic dicarboxylic acids>>> Examples of aromatic dicarboxylic acids include aromatic dicarboxylic acids having 6 to 20 carbon atoms. More specific examples of aromatic dicarboxylic acids include orthophthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, and 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid.
[0031] Among these dibasic acids, from the viewpoint of biodegradability, non-aromatic dicarboxylic acids are preferred, aliphatic dicarboxylic acids are more preferred, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid represented by the following formula (1) are even more preferred, adipic acid, azelaic acid, and sebacic acid are even more preferred, and adipic acid and sebacic acid are particularly preferred. Two or more kinds of dibasic acids may be used in combination.
[0032] [ka] Formula (1) (In formula (1), n represents an integer of 4 to 8.)
[0033] <<Glycol>> The glycol may be a non-aromatic glycol or an aromatic glycol.
[0034] <<<Non-aromatic glycols>>> The non-aromatic glycol may be an aliphatic glycol or an alicyclic glycol, and the number of carbon atoms of the non-aromatic glycol may be, for example, 1 to 15.
[0035] Examples of aliphatic glycols include ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, neopentyl glycol, cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2-methylpentane-2,4-diol, 3,3-dimethyl-1,2-butanediol, 2,3-dimethyl-2,3-butanediol, butylethylpropanediol, 1,9-nonanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol.
[0036] Examples of the alicyclic glycol include alicyclic diols having a carbon number of 6 to 15. Examples of the alicyclic diol include 1,3-bis(2-hydroxypropyl)cyclopentane, 1,3-bis(2-hydroxybutyl)cyclopentane, 1,4-bis(hydroxymethyl)cyclohexane, 1,4-bis(2-hydroxypropyl)cyclohexane, and 1,4-bis(2-hydroxybutyl)cyclohexane.
[0037] The aromatic glycol may, for example, be an aromatic glycol having 6 to 20 carbon atoms. Examples of aromatic glycols having 6 to 20 carbon atoms include 1,3-benzenedimethanol, 1,4-benzenedimethanol, 1,4-benzenediethanol, and 1,4-bis(2-hydroxyethoxy)benzene.
[0038] Among these glycols, from the viewpoint of biodegradability, non-aromatic glycols are preferred, aliphatic glycols are more preferred, and glycols represented by the following formula (2) are particularly preferred. Two or more types of glycols may be used in combination.
[0039] [ka] Formula (2) In formula (2), A represents a carbon atom or an oxygen atom, R1 represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms or a hydroxyl group, and R2 represents a hydrogen atom or a hydroxyl group. l and m each independently represent an integer of 0 to 4, provided that l+m is 1 or greater. However, when A is an oxygen atom, there is no H bonded to R1 or A. Also, either R1 or R2 is a hydroxyl group, but both R1 and R2 are not hydroxyl groups.
[0040] Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclopropyl group, an n-butyl group, an i-butyl group, an s-butyl group, a t-butyl group, a cyclobutyl group, a 1-methyl-cyclopropyl group, a 2-methyl-cyclopropyl group, etc. Among these, a methyl group is preferred from the viewpoint of excellent reactivity.
[0041] Among the glycols represented by formula (2), 1,3-propanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-(2-hydroxyethoxy)ethanol, and 3-(3-hydroxypropoxy)propan-1-ol are preferred, and from the viewpoint of excellent biodegradability, 2-methyl-1,3-propanediol and 3-methyl-1,5-pentanediol are more preferred.
[0042] The biodegradable structural unit is derived from the structure, and the structure can be obtained by arbitrarily selecting the above dibasic acid and the above glycol, and subjecting them to an esterification reaction by a known method. Although not particularly limited, a suitable example of a biodegradable constitutional unit is, for example, a constitutional unit represented by the following formula (3A) or the following formula (3B).
[0043] [ka] Formula (3A)
[0044] [ka] Formula (3B) (In formula (3A) and formula (3B), R3 represents a hydrogen atom or a methyl group, l and m each independently represent an integer of 0 to 4, l+m being 1 or greater, and n represents an integer of 4 to 8.)
[0045] In formula (3A), it is preferable that R3 is a methyl group, l and m are each independently an integer of 1 or 2, and n is an integer of 4-8.
[0046] To form a biodegradable polymer (x), it is preferable to use the dibasic acid (Ia) described below among the dibasic acids exemplified above. The dibasic acid (Ia) forming the biodegradable polymer (x) is preferably at least one selected from the group consisting of adipic acid, azelaic acid, and sebacic acid.
[0047] In order to form a biodegradable polymer (x), it is preferable to use the following glycol (Ib) among the glycols exemplified above. The glycol (Ib) forming the biodegradable polymer (x) is preferably at least one selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol.
[0048] The structural unit exhibiting biodegradability in the polymer (x) is, A structural unit derived from a structure in which ethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which diethylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and adipic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and adipic acid are bonded, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which diethylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,2-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-propylene glycol and sebacic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,3-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,4-butanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,6-hexanediol and sebacic acid are bonded, a structural unit derived from a structure in which 1,9-nonanediol and sebacic acid are bonded, A structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, 1,6-hexanediol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol, diethylene glycol, and adipic acid are bonded together, a structural unit derived from a structure in which ethylene glycol, diethylene glycol, 2-methyl-1,3-propanediol, and adipic acid are bonded together, A structural unit derived from a structure in which ethylene glycol and sebacic acid are bonded, and a structural unit derived from a structure in which ethylene glycol, 2-methyl-1,3-propanediol, adipic acid, and sebacic acid are bonded, It is preferable that the compound is at least one selected from the group consisting of the above.
[0049] Among these, the structural unit exhibiting biodegradability in the polymer (x) is More preferably, the structural unit is any one of a structural unit derived from a structure in which 2-methyl-1,3-propanediol and adipic acid are bonded, a structural unit derived from a structure in which 2-methyl-1,3-propanediol and sebacic acid are bonded, and a structural unit derived from a structure in which 3-methyl-1,5-pentanediol and adipic acid are bonded.
[0050] Described in terms of specific structural formulas, examples include constitutional units represented by the following formulas (3-1) to (3-3), etc.
[0051] [ka] Formula (3-1)
[0052] [ka] Formula (3-2)
[0053] [ka] Formula (3-3)
[0054] <Polymer (y) Containing a Non-biodegradable Structural Unit> The polymer (y) contains a non-biodegradable structural unit. The non-biodegradable structural unit contained in the polymer (y) may be used alone or in combination of two or more kinds. The non-biodegradable structural unit is not particularly limited as long as it is non-biodegradable and can form a copolymer with a biodegradable structural unit.
[0055] The dibasic acids and glycols used to form the polymer (y) are as exemplified above in the section <Polymer (x) having a structural unit exhibiting biodegradability>. The seawater decomposition rate of the structure obtained by binding varies depending on the combination of the types of dibasic acids and glycols. Therefore, in order to form a non-biodegradable polymer (y), it is advisable to appropriately select preferred types from the dibasic acids and glycols exemplified above so that the structure obtained by binding exhibits a seawater decomposition rate of less than 15%. The non-biodegradable structural unit is not particularly limited, but preferably contains a structural unit derived from a structure in which a dibasic acid other than the dibasic acid represented by the above formula (1) described in the above section <Polymer (x) having a structural unit exhibiting biodegradability> is bonded to a glycol.
[0056] The non-biodegradable structural unit is not particularly limited, and examples thereof include structural units derived from butylene succinate, butylene adipate terephthalate, etc. Among these, the non-biodegradable structural unit in the polymer (y) is preferably either a structural unit derived from butylene succinate represented by the following formula (4-1) (corresponding to a structural unit derived from a structure in which 1,4 butanediol and succinic acid are bonded) or a structural unit derived from butylene adipate terephthalate represented by the following formula (4-2) (a structural unit derived from a structure in which 1,4 butanediol, adipic acid, and terephthalic acid are bonded).
[0057] [ka] Formula (4-1)
[0058] [ka] Formula (4-2)
[0059] <Any polymer containing other structural units> The copolyester resin of the present invention may contain any polymer having other structural units than those described above, as necessary, within the scope of not impairing the effects of the present invention.
[0060] The copolyester resin of the present invention is a block copolymer containing a biodegradable block (X) and a non-biodegradable block (Y), and is obtained by copolymerizing a polymer (x) containing the above-mentioned biodegradable structural unit with a polymer (y) containing the above-mentioned non-biodegradable structural unit. Although not particularly limited, suitable examples of the copolyester resin of the present invention include those represented by the following formulae (5) to (8).
[0061] [ka] Formula (5) (In formula (5), o, p, and q each independently represent a positive integer.)
[0062] [ka] Formula (6) (In formula (6), o, p, and q each independently represent a positive integer.)
[0063] [ka] Formula (7) (In formula (7), o, p, and q each independently represent a positive integer.)
[0064] [ka] Formula (8) (In formula (8), o, p, q and r each independently represent a positive integer.)
[0065] The content of the biodegradable block (X) constituting the copolyester resin is preferably 5% by mass or more, more preferably 10% by mass or more, based on the copolyester resin (100% by mass), from the viewpoint of obtaining sufficient biodegradability. On the other hand, the content is preferably 50% by mass or less, more preferably 45% by mass or less, from the viewpoint of obtaining sufficient thermoformability. These upper and lower limits can be used in any combination. The content is preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 45% by mass or less.
[0066] The content of the non-biodegradable block (Y) constituting the copolyester resin is preferably 50% by mass or more, more preferably 55% by mass or more, based on the copolyester resin (100% by mass), from the viewpoint of obtaining sufficient thermoformability. On the other hand, the content is preferably 95% by mass or less, more preferably 90% by mass or less, from the viewpoint of obtaining sufficient biodegradability. These upper and lower limits can be used in any combination. The content is preferably 50% by mass or more and 95% by mass or less, more preferably 55% by mass or more and 90% by mass or less.
[0067] The molar ratio (X / Y) of the biodegradable block (X) and the non-biodegradable block (Y) is 1 / 99 or more, preferably 5 / 95 or more, more preferably more than 5 / 95, even more preferably 10 / 90 or more, and particularly preferably 15 / 85 or more, from the viewpoint of obtaining sufficient biodegradability. On the other hand, the molar ratio (X / Y) is 95 / 5 or less, preferably 80 / 20 or less, more preferably 70 / 30 or less, and particularly preferably 50 / 50 or less, from the viewpoint of obtaining sufficient thermoformability. These upper and lower limits can be used in any combination. The molar ratio (X / Y) is 1 / 99 or more and 95 / 5 or less, preferably 5 / 95 or more and 95 / 5 or less, more preferably more than 5 / 95 and 95 / 5 or less, even more preferably 10 / 90 or more and 80 / 20 or less, even more preferably 15 / 85 or more and 70 / 30 or less, and particularly preferably 15 / 85 or more and 50 / 50 or less.
[0068] From the viewpoint of obtaining sufficient biodegradability, the average sequence length of the biodegradable block (X) is preferably greater than 1.2, 4.0 or more, more preferably 4.2 or more, even more preferably 5.0 or more, and particularly preferably 5.5 or more. On the other hand, from the viewpoint of obtaining sufficient thermoformability, the average sequence length is preferably 30 or less, more preferably 20 or less, and even more preferably 15 or less. These upper and lower limits can be used in any combination. The average sequence length is greater than 1.2 and 30 or less, preferably 4.0 or more and 30 or less, more preferably 4.2 or more and 20 or less, even more preferably 5.0 or more and 20 or less, and particularly preferably 5.5 or more and 15 or less.
[0069] The average sequence length of the polymer block (Y) is preferably 4.0 or more, more preferably 4.2 or more, and even more preferably 5.0 or more, from the viewpoint of obtaining sufficient thermoformability. On the other hand, the average sequence length is preferably 40.0 or less, more preferably 35 or less, and even more preferably 30.0 or less, from the viewpoint of obtaining sufficient biodegradability. Any combination of these upper and lower limits can be used. The average sequence length is preferably 4.0 or more and 40.0 or less, more preferably 4.2 or more and 35 or less, and even more preferably 5.0 or more and 30.0 or less.
[0070] The number average molecular weight (Mn) of the copolyester resin measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably 5,000 or more, more preferably 7,000 or more, even more preferably 8,000 or more, and particularly preferably 10,000 or more, from the viewpoint of processability and handling. On the other hand, the number average molecular weight (Mn) is preferably 150,000 or less, more preferably 100,000 or less, even more preferably 70,000 or less, and particularly preferably 50,000 or less, from the viewpoint of obtaining sufficient biodegradability. These upper and lower limits can be used in any combination. The number average molecular weight (Mn) is preferably 5,000 or more and 150,000 or less, preferably 5,000 or more and 100,000 or less, more preferably 7,000 or more and 100,000 or less, more preferably 7,000 or more and 70,000 or less, even more preferably 10,000 or more and 70,000 or less, and even more preferably 8,000 or more and 50,000 or less.
[0071] The weight average molecular weight (Mw) of the copolyester resin measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably 7,000 or more, more preferably 10,000 or more, even more preferably 15,000 or more, and particularly preferably 20,000 or more, from the viewpoint of processability and handling. On the other hand, the weight average molecular weight (Mw) is preferably 200,000 or less, more preferably 150,000 or less, and even more preferably 100,000 or less, from the viewpoint of obtaining sufficient biodegradability. These upper and lower limits can be used in any combination. The weight average molecular weight (Mw) is preferably 7,000 to 200,000, preferably 10,000 to 200,000, more preferably 10,000 to 150,000, more preferably 15,000 to 150,000, even more preferably 15,000 to 100,000, and even more preferably 20,000 to 100,000.
[0072] In the copolyester resin, the molecular weight distribution (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) in terms of polystyrene measured by GPC by the number average molecular weight (Mn) is preferably 4.5 or less, more preferably 4.0 or less, even more preferably 3.7 or less, and particularly preferably 3.5 or less, from the viewpoint of obtaining a resin having a low degree of dispersion and exhibiting desired properties.
[0073] From the viewpoint of biodegradability, the randomness of the copolyester resin is preferably 0.07 or more, more preferably 0.09 or more. On the other hand, from the viewpoint of thermoformability, the randomness of the copolyester resin is preferably 1.0 or less, more preferably 0.9 or less. Any combination of these upper and lower limits can be used. The randomness of the copolyester resin is preferably 0.07 or more and 1.0 or less, more preferably 0.09 or more and 0.9 or less.
[0074] The melting point (Tm) of the copolyester resin is preferably 40° C. or higher, more preferably 65° C. or higher, more preferably 70° C. or higher, even more preferably 95° C. or higher, even more preferably 100° C. or higher, and particularly preferably 102° C. or higher. On the other hand, the upper limit of the thermal decomposition temperature of the copolyester resin is not particularly limited, but is usually 250° C. or lower. When the melting point is within the above range, the thermal processability during molding is excellent.
[0075] The biodegradability of the copolyester resin in a seawater environment is 15% or more because the copolyester resin needs to exhibit the "biodegradability" defined in the present invention, but the seawater decomposition rate is more preferably 24% or more, even more preferably 40% or more, and particularly preferably 50% or more. Inoculum source: Seawater collected from the coast of Akane Bay (near Akanehama, Narashino City, Chiba Prefecture) was used as the inoculum source. Biodegradability measurement method: Soda lime (carbon dioxide absorbent) and a pressure sensor (WTW, OxiTop-IDS (registered trademark)) are attached to a test bottle, and the BOD (biological oxygen demand) is measured under the conditions below to calculate the biodegradability. Culture temperature: 27℃, dark place Culture period: 28 days Calculation of biodegradability: The biodegradability of the sample is calculated based on the following formula. Biodegradability (%)=(BOD0-BODB) / ThOD×100 BOD0: Biochemical oxygen demand of the sample (measured value: mg) BODB: Average biochemical oxygen demand in blank test (measured value: mg) ThOD: Theoretical oxygen demand required for complete oxidation of the sample (calculated value: mg)
[0076] The biodegradability of the copolyester resin in a freshwater environment is preferably 15% or more, more preferably 24% or more, even more preferably 40% or more, and particularly preferably 50% or more. In this specification, the biodegradability of the copolyester resin in a freshwater environment is a value calculated in the same manner as the seawater degradability described above, except that the inoculum source is river water collected from the Inagawa River (near Momozono, Ikeda City, Hyogo Prefecture).
[0077] The biodegradability of the copolyester resin in a soil environment is preferably 15% or more, more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more. In this specification, the biodegradability of the copolyester resin in a soil environment is a value calculated in the same manner as the seawater degradability described above, except that the inoculum source is soil collected from Oshinotsuka Community Farm (near Oshinotsuka, Sakura City, Chiba Prefecture).
[0078] The compost decomposition rate of the copolyester resin under composting conditions is preferably 15% or more, more preferably 24% or more, further preferably 40% or more, and particularly preferably 50% or more. In this specification, the compost decomposition rate of the copolyester resin under compost conditions is a value determined by a method in accordance with JIS K6953-1:2011. Culture temperature: 58℃ Culture period: 28 days
[0079] <Copolyester resin having triad units of units (A) and units (B)> The copolyester resin of the present invention preferably contains two types of triad units (units (A) and units (B)) that exhibit biodegradability. Of the two types of biodegradable triad units contained in the copolyester resin of the present invention, one unit (unit (A)) is derived from a structure represented by "first glycol / dibasic acid / first glycol" in which a first glycol is bonded to a dibasic acid, and the other unit (unit (B)) is derived from a structure represented by "second glycol / dibasic acid / second glycol" in which a second glycol different from the first glycol is bonded to a dibasic acid.
[0080] Preferred combinations of the two types of biodegradable triad units (units (A) and units (B)) contained in the copolyester resin of the present invention include, for example, any of the following (i) to (iii). (i) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3 propanediol, adipic acid, and 2-methyl-1,3 propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4 butanediol, adipic acid, and 1,4 butanediol are bonded" or (ii) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3 propanediol, sebacic acid, and 2-methyl-1,3 propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4 butanediol, sebacic acid, and 1,4 butanediol are bonded", or (iii) It is preferable that the unit (A) is a triad unit derived from a "structure in which 3-methyl-1,5-pentanediol, adipic acid, and 3-methyl-1,5-pentanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, adipic acid, and 1,4-butanediol are bonded".
[0081] (Method of producing copolyester resin) The copolyester resin of the present invention can be produced by a general method for producing a copolyester resin. However, it is preferable to use a transesterification reaction, since it is easier to obtain a copolyester resin having a desired average chain length.
[0082] The method for producing a copolyester resin of the present invention, in which a biodegradable block (X) derived from a polymer (x) containing a biodegradable structural unit and a non-biodegradable block (Y) derived from a polymer (y) containing a non-biodegradable structural unit are combined, preferably comprises a step of subjecting the polymer (x) and the polymer (y) to a transesterification reaction to obtain a block copolymer containing the biodegradable block (X) and the non-biodegradable block (Y).
[0083] A preferred embodiment of the method for producing a copolyester resin of the present invention includes, for example, a step of synthesizing a polymer (x) containing a biodegradable structural unit by polycondensing a hydroxyalkanoic acid or a dibasic acid with a glycol; A step of synthesizing a polymer (y) containing a non-biodegradable structural unit; and a step of subjecting polymer (x) and polymer (y) to a transesterification reaction to obtain a block copolymer containing a biodegradable block (X) and a non-biodegradable block (Y).
[0084] <Step of synthesizing polymer (x) and polymer (y)> The synthesis method of the polymer (x) and the polymer (y) is not particularly limited, and can be carried out by using a general synthesis method of a polyester resin. For example, the case where the polymer (y) is a polyester resin containing a structural unit derived from a structure in which a dibasic acid other than the dibasic acid represented by the above formula (1) and a glycol are bonded will be described below.
[0085] The dibasic acid and glycol used as raw materials in the synthesis of polymer (x) or polymer (y) can be those described in the section on polymer (x) containing a biodegradable structural unit or polymer (y) containing a non-biodegradable structural unit. The raw materials for the synthesis of polymer (x) or polymer (y) may contain other raw materials in addition to dibasic acid and glycol. The other raw materials are not particularly limited, but may include, for example, trivalent or higher polyhydric alcohols, trivalent or higher polycarboxylic acids, etc.
[0086] The blending ratio of the dibasic acid to the glycol is not particularly limited, but is preferably from 90:10 to 50:50, and more preferably from 80:20 to 50:50, in mass ratio (dibasic acid:glycol).
[0087] The reaction may be carried out without a catalyst or in the presence of a catalyst. Examples of the catalyst used in the reaction include acid catalysts. Examples of the acid catalyst include tin catalysts such as monobutyltin oxide and dibutyltin oxide, titanium catalysts such as titanium tetraisopropoxide and titanyl acetylacetonate, and zirconia catalysts such as tetra-butyl-zirconate. It is preferable to use a titanium catalyst in order to increase the activity of the transesterification reaction and the esterification reaction. Examples of the titanium catalyst include titanium tetramethoxide, titanium tetraethoxide, titanium tetraisopropoxide, titanium tetra n-propoxide, titanium tetra n-butoxide, tetrakis(2-ethylhexyloxy)titanium, and tetrastearyloxytitanium. In terms of stability in handling and activity as a catalyst, titanium tetraisopropoxide is preferred. The amount of the catalyst used is usually in the range of 0.001 to 5.0% by mass based on the total mass of the dibasic acid and the glycol.
[0088] The reaction for synthesizing the polymer (x) or the polymer (y) generates by-products such as water and lower alcohols. These are removed from the reaction system during the reaction process, which makes it easier for the condensation reaction to proceed.
[0089] The reaction temperature is not particularly limited, but is usually 50 to 300°C. The reaction atmosphere may be air or an inert gas atmosphere such as nitrogen gas or argon gas. The reaction time is usually 1 to 48 hours, but the reaction is preferably carried out until the dibasic acid or glycol as the raw material no longer remains in the reaction system. The progress of the reaction can be monitored, for example, by tracking the decrease in the dibasic acid by measuring the acid value.
[0090] <Production process of copolyester resin by transesterification reaction> The method for synthesizing a polymer by transesterification is not particularly limited, and can be carried out using a general method for synthesizing a polymer by transesterification.
[0091] The catalyst used in the transesterification reaction is preferably a titanium catalyst. Examples of the titanium catalyst include titanium tetramethoxide, titanium tetraethoxide, titanium tetraisopropoxide, titanium tetra n-propoxide, titanium tetra n-butoxide, tetrakis(2-ethylhexyloxy)titanium, and tetrastearyloxytitanium. In terms of stability in handling and activity as a catalyst, titanium tetraisopropoxide is preferred. The amount of the catalyst used is usually in the range of 0.001 to 5.0% by mass based on the total mass of the polymer (x) and the polymer (y).
[0092] The reaction temperature is not particularly limited, but is usually 50 to 300° C. The reaction atmosphere may be air or an inert gas atmosphere such as nitrogen gas or argon gas. The reaction time is usually 1 to 48 hours.
[0093] (Polyurethane) One embodiment of the copolyester resin obtained as described above is polyurethane. The polyurethane can be obtained by reacting the copolyester of the present invention with a polyisocyanate. If necessary, a polyol other than the copolyester, a chain extender, a chain terminator, or a crosslinking agent may be used in combination. Specifically, polyurethane is obtained by reacting a polyol with a polyisocyanate, and at least the copolyester of the present invention is used as the polyol. Thus, polyurethane is a reaction product obtained by reacting a polyol with a polyisocyanate, and polyurethane has structural units derived from the polyol and structural units derived from the polyisocyanate, and at least structural units derived from the copolyester of the present invention.
[0094] The copolyester of the present invention is preferably a polyester polyol. The polyester polyol may be a condensation polyester polyol. The condensation polyester polyol may be, for example, a reaction product of a low molecular weight polyhydric alcohol (ethylene glycol (EG), diethylene glycol, propylene glycol (PG), dipropylene glycol, (1,3- or 1,4-) butanediol, pentanediol, neopentyl glycol, hexanediol, cyclohexane dimethanol, glycerin, 1,1,1-trimethylolpropane (TMP), 1,2,5-hexanetriol, low molecular weight polyol such as pentaerythritol, sugar such as sorbitol, etc.) and a polybasic carboxylic acid (glutaric acid, adipic acid, azelaic acid, fumaric acid, maleic acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, terephthalic acid, isophthalic acid, dimer acid, pyromellitic acid, oligomer acid, etc.).
[0095] Examples of chain extenders include aliphatic polyol compounds such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, hexamethylene glycol, saccharose, methylene glycol, glycerin, sorbitol, and neopentyl glycol; bisphenol A, 4,4'-dihydroxydiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl sulfone, hydrogenated bisphenol A, and hydroquinone. Aromatic polyol compounds of the above; water; amine compounds such as ethylenediamine, 1,2-propanediamine, 1,6-hexamethylenediamine, piperazine, 2-methylpiperazine, 2,5-dimethylpiperazine, isophoronediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, 1,2-cyclohexanediamine, 1,4-cyclohexanediamine, aminoethylethanolamine, hydrazine, diethylenetriamine, triethylenetetramine, and isophoronediamine can be used. These chain extenders may be used alone or in combination of two or more. Among them, aliphatic polyol compounds are preferred, and neopentyl glycol is more preferred.
[0096] The content of the copolyester of the present invention in 100% by mass of polyol is preferably from 10 to 100% by mass, and more preferably from 50 to 100% by mass.
[0097] Examples of polyisocyanates include 1,3- and 1,4-phenylene diisocyanate, 1-methyl-2,4-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-2,5-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-3,5-phenylene diisocyanate, 1-ethyl-2,4-phenylene diisocyanate, 1-isopropyl-2,4 -phenylene diisocyanate, 1,3-dimethyl-2,4-phenylene diisocyanate, 1,3-dimethyl-4,6-phenylene diisocyanate, 1,4-dimethyl-2,5-phenylene diisocyanate, diethylbenzene diisocyanate, diisopropylbenzene diisocyanate, 1-methyl-3,5-diethylbenzene diisocyanate, 3-methyl-1,5-diethylbenzene-2,4-diisocyanate, 1,3,5- Triethylbenzene-2,4-diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, 1-methyl-naphthalene-1,5-diisocyanate, naphthalene-2,6-diisocyanate, naphthalene-2,7-diisocyanate, 1,1-dinaphthyl-2,2'-diisocyanate, biphenyl-2,4'-diisocyanate, biphenyl-4,4'-diisocyanate, 3-3'-dimethylbiisocyanate Aromatic polyisocyanates such as phenyl-4,4'-diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, diphenylmethane-2,4-diisocyanate, and toluene diisocyanate; aliphatic polyisocyanates such as tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, and trimethylhexamethylene diisocyanate;Alicyclic polyisocyanates such as 1,3-cyclopentylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, 1,3-di(isocyanatemethyl)cyclohexane, 1,4-di(isocyanatemethyl)cyclohexane, lysine diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate, 2,2'-dicyclohexylmethane diisocyanate, and 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate can be used. These may be used alone or in combination of two or more. Among them, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-diphenylmethane diisocyanate, and toluene diisocyanate are more preferred.;
[0098] In order to control the molecular weight of the resulting polyurethane, a chain terminator having one active hydrogen group may be used as necessary. Examples of these chain terminators include aliphatic monohydroxy compounds having a hydroxyl group, such as methanol, ethanol, propanol, butanol, and hexanol, and aliphatic monoamines having an amino group, such as morpholine, diethylamine, dibutylamine, monoethanolamine, and diethanolamine. These may be used alone or in combination of two or more.
[0099] For the purpose of increasing the heat resistance and strength of the resulting polyurethane, a crosslinking agent having three or more active hydrogen groups or isocyanate groups can be used as necessary.
[0100] The polyurethane can be obtained by a known polyurethane manufacturing method. Specifically, for example, a manufacturing method can be mentioned in which a polyol, a polyisocyanate, and the chain extender are charged and reacted. These reactions are preferably carried out at a temperature of 50 to 100°C for 3 to 10 hours. The reaction may also be carried out in an organic solvent.
[0101] Examples of the organic solvent that can be used include ketone solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, methyl ethyl ketone, methyl-n-propyl ketone, acetone, and methyl isobutyl ketone; ester solvents such as methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, isopropyl acetate, isobutyl acetate, isobutyl acetate, and sec-butyl acetate; etc. These organic solvents may be used alone or in combination of two or more.
[0102] The content of the structural units derived from the copolyester of the present invention in 100% by mass of polyurethane is preferably from 10 to 98% by mass, and more preferably from 20 to 98% by mass. This tends to produce a more favorable effect. In this specification, the content of each structural unit in the polyurethane is measured by NMR.
[0103] The number average molecular weight (Mn) of the polyurethane may have a lower limit of 5,000 or more, 6,000 or more, 7,000 or more, 8,000 or more, or 10,000 or more, and an upper limit of 1,000,000 or less, 500,000 or less, 100,000 or less, 500,000 or less, or 15,000 or less. Any combination of these upper and lower limits may be used. The number average molecular weight (Mn) of the polyurethane may be 5,000 to 1,000,000, 6,000 to 500,000, 7,000 to 100,000, 8,000 to 500,000, or 10,000 to 15,000. Within the above range, the effect tends to be more favorably obtained.In this specification, the number average molecular weight (Mn) of the polyurethane is a value measured by GPC.
[0104] (Resin composition) Examples of the resin composition of the present embodiment include a thermoplastic resin composition containing the copolyester or polyurethane of the present embodiment described above, and a thermosetting resin composition.
[0105] <Thermoplastic resin composition> When the resin composition of the present embodiment is a thermoplastic resin composition, for example, it may further contain other resins, a crystallization nucleating agent, a heat stabilizer, a hydrolysis inhibitor, other additives, and the like, as necessary.
[0106] <<Crystallization nucleating agent>> The crystallization nucleating agent used in the thermoplastic resin composition according to the present embodiment may be any crystallization nucleating agent used in thermoplastic resins derived from biomass resources, such as polylactic acid and polybutylene succinate. For example, talc-based nucleating agents, nucleating agents made of metal salt-based materials having a phenyl group, and nucleating agents made of benzoyl compounds are preferably used. Other known crystallization nucleating agents, such as lactate, benzoate, silica, and phosphate salts, may also be used.
[0107] <<Heat stabilizers and hydrolysis inhibitors>> The thermoplastic resin composition of the present embodiment preferably contains a phenol-based antioxidant and a phosphite-based antioxidant as a heat stabilizer for the resin composition, and a carbodiimide compound-based hydrolysis inhibitor, such as polycarbodiimide resin (product name: Carbodilite, manufactured by Nisshinbo Chemical Co., Ltd.), as a hydrolysis inhibitor. The heat stabilizer and hydrolysis inhibitor to be added may be one selected from the above three types of additives, but the above two types of heat stabilizers and hydrolysis inhibitors have different functions, and it is preferable that each additive is added together. The amount of heat stabilizer and hydrolysis inhibitor to be added varies depending on the type, but generally, it is preferable that each is about 0.1 to 5 parts by mass per 100 parts by mass of the thermoplastic resin composition.
[0108] <<Other additives>> It is preferable to further add a silicone-based flame retardant, an organometallic salt-based flame retardant, an organophosphorus-based flame retardant, a metal oxide-based flame retardant, a metal hydroxide-based flame retardant, etc. to the thermoplastic resin composition of this embodiment, which improves the flame retardancy and inhibits the spread of fire, and also improves the fluidity of the biodegradable resin composition, thereby ensuring better moldability.
[0109] A filler can be added to the thermoplastic resin composition of the present embodiment. Examples of the filler include talc, mica, montmorillonite, and kaolin. These fillers act as crystal nuclei to promote crystallization of the copolyester, improving the impact strength and heat resistance of the molded article. In addition, the rigidity of the molded article can be increased.
[0110] The thermoplastic resin composition of the present embodiment may be appropriately blended with various additives such as antioxidants, antiblocking agents, colorants, flame retardants, release agents, antifogging agents, surface wettability improvers, incineration aids, lubricants, dispersion aids, various surfactants, plasticizers, compatibilizers, weather resistance improvers, ultraviolet absorbers, processing aids, antistatic agents, colorants, lubricants, and release agents. As the plasticizer, any known plasticizer generally used as a plasticizer for polymers can be used without particular limitation, and examples thereof include polyester plasticizers, glycerin-based plasticizers, polyvalent carboxylic acid ester-based plasticizers, polyalkylene glycol-based plasticizers, and epoxy-based plasticizers. There are no particular limitations on the compatibilizer as long as it functions as a compatibilizer for copolymer A and copolymer B. Examples of the compatibilizer include inorganic fillers, glycidyl compounds, polymer compounds grafted or copolymerized with acid anhydrides, and organometallic compounds, and one or more of these may be used. By kneading these materials, the heat resistance, bending strength, impact strength, flame retardancy, etc. are improved, which further promotes the application of the materials to molded articles such as housings for electronic devices, such as notebook computers and mobile phones.
[0111] In addition, various fillers known in the art can be blended as the filler. As functional additives, chemical fertilizers, soil conditioners, plant activators, etc. can also be added. The fillers are broadly classified into inorganic fillers and organic fillers. These can be used alone or in a mixture of two or more kinds.
[0112] Examples of inorganic fillers include anhydrous silica, mica, talc, titanium oxide, calcium carbonate, diatomaceous earth, allophane, bentonite, potassium titanate, zeolite, sepiolite, smectite, kaolin, kaolinite, glass, limestone, carbon, wollastonite, calcined perlite, silicates such as calcium silicate and sodium silicate, hydroxides such as aluminum oxide, magnesium carbonate and calcium hydroxide, salts such as ferric carbonate, zinc oxide, iron oxide, aluminum phosphate and barium sulfate, etc. The content of the inorganic filler in the entire composition is usually 1 to 80% by weight, preferably 3 to 70% by weight, and more preferably 5 to 60% by weight. Examples of organic fillers include raw starch, processed starch, pulp, chitin, chitosan, coconut shell powder, wood powder, bamboo powder, bark powder, kenaf powder, straw powder, etc. These can be used alone or in a mixture of two or more. The amount of organic filler added is usually 0.01 to 70% by weight of the total composition.
[0113] The composition can be prepared by any of the conventionally known mixing / kneading techniques. As the mixer, a horizontal cylindrical type, V-shaped type, double cone type mixer, a blender such as a ribbon blender or a super mixer, or various continuous mixers can be used. As the kneader, a batch type kneader such as a roll or an internal mixer, a one-stage type or two-stage type continuous kneader, a twin screw extruder, a single screw extruder, or the like can be used. As the kneading method, a method of adding various additives, fillers, and thermoplastic resins to the heated and melted material and blending them can be mentioned. In addition, a blending oil or the like can be used for the purpose of uniformly dispersing the various additives.
[0114] <Thermosetting resin composition> When the resin composition of the present embodiment is a thermosetting resin composition, it contains, for example, another resin, the copolyester of the present embodiment having reactive groups such as a hydroxyl group or a carboxyl group as a thermosetting resin main component, and further contains a curing agent such as an isocyanate curing agent or a polyamine curing agent that can thermally react with the reactive groups.
[0115] Examples of the curing agent according to the present embodiment include polyisocyanates having an aromatic structure in their molecular structure, such as tolylene diisocyanate, diphenylmethane diisocyanate, polymeric diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and xylylene diisocyanate, and compounds in which a part of the isocyanate groups of these polyisocyanates is modified with carbodiimide; allophanate compounds derived from these polyisocyanates; polyisocyanates having an alicyclic structure in their molecular structure, such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexylisocyanate), and 1,3-(isocyanatomethyl)cyclohexane; linear aliphatic polyisocyanates, such as 1,6-hexamethylene diisocyanate, lysine diisocyanate, and trimethylhexamethylene diisocyanate, and allophane derivatives thereof. allophanate forms derived from these polyisocyanates; biuret forms derived from these polyisocyanates; trimethylolpropane-modified adducts; polyfunctional isocyanates such as polyisocyanates which are reaction products of the above-mentioned various polyisocyanates with polyol components; polyethylene polyamines such as ethylene diamine, diethylene triamine, triethylene tetramine, tetraethylene pentamine, pentaethylene hexamine, hexaethylene heptamine, heptaethylene octamine, octaethylene nonamine, nonaethylene decamine, piperazine, and N-aminoalkyl piperazines having an alkyl chain with 2 to 6 carbon atoms; and amine compounds such as 3-aminomethyl-3,5,5-trimethylcyclohexylamine (isophorone diamine, or IPDA).
[0116] <Cured product of resin composition> The cured product of the resin composition of the present embodiment is a cured product of the resin composition as the above-mentioned thermoplastic resin composition, or a cured product of the resin composition as the above-mentioned thermosetting resin composition.
[0117] The polymers described herein can be used in a wide variety of applications, including artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, elastic fibers, urethane raw materials, automobile parts, sporting goods, vibration-proofing materials, vibration-damping materials, fiber treatment agents, and binders.
[0118] Copolyesters can be used in a wide range of applications, including artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, elastic fibers, urethane raw materials, automotive parts, and sporting goods.
[0119] Polyurethane can be used in a wide range of applications, including artificial leather, synthetic leather, shoes, thermoplastic resins, foamed resins, thermosetting resins, paints, laminating adhesives, vibration-proofing materials, vibration-damping materials, automobile parts, sporting goods, textile treatment agents, and binders.
[0120] (Coating agent) The coating agent contains the copolyester resin of the present invention, and further contains other components such as other resins, water, and organic solvents, as necessary.
[0121] The coating agent can be applied to various substrates. An example of the application of the coating agent will be described below. The coating agent is used, for example, for surface coating of the substrate of a food packaging container. Examples of the substrate include plastic films such as styrene-based resin films, polyolefin-based resin films, polyester-based resin films, nylon-based resin films, and laminates thereof. Examples of the substrate include paper, metal-deposited films, aluminum foils, and the like. The coating agent is preferably used for biodegradable substrates. Examples of the biodegradable substrate include paper, polyester-based films, polyolefin-based films, and starch-based films. The coating agent can be used as an ink, an adhesive, or the like.
[0122] (Ink) The ink contains the copolyester resin of the present invention and a colorant, and further contains other components such as a pigment dispersant, water, and an organic solvent, as necessary. The ink is, for example, a printing ink. The ink may be, for example, a water-based ink or an ink that does not contain water (solvent-based ink).
[0123] (glue) The adhesive contains the copolyester resin of the present invention, and further contains other components such as other resins, a curing agent, and an organic solvent, as necessary. The adhesive can also be used as an adhesive composition for lamination, which is laminated onto the various substrates described above to produce composite films used primarily as packaging materials for foods, medicines, detergents, and the like. Such adhesives include, for example, two-component curing adhesives containing the copolyester resin of the present invention, polymer polyol, and polyisocyanate, and one-component adhesives made of acrylic resin, urethane resin, and ethylene-vinyl acetate copolymer. These adhesives may be solvent-based, solventless, aqueous, or alcohol-based adhesives, as required.
[0124] (Sheet) The sheet is made of a resin composition containing the copolyester resin of the present invention. The resin composition may contain other resins and various additives in addition to the copolyester resin of the present invention. Examples of the various additives include plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, lubricants, antiblocking agents, and heat stabilizers. Examples of the sheet include a non-oriented sheet, a biaxially oriented sheet, and a foamed sheet. The uses of the sheet are not particularly limited, but it can be used in a wide range of applications, such as food packaging containers, construction materials, home electrical appliances, and miscellaneous goods.
[0125] (film) The film is made of a resin composition containing the copolyester resin of the present invention. The resin composition may contain other resins and various additives in addition to the copolyester resin of the present invention. Examples of the various additives include plasticizers, antistatic agents, antioxidants, ultraviolet absorbers, lubricants, antiblocking agents, and heat stabilizers. Examples of the film include unstretched films, biaxially stretched films, and uniaxially stretched films, and can be produced by, for example, melting pellets of the film raw material in an extruder and forming the film into a film using a T-die or inflation method. In the T-die method, a biaxially stretched film is obtained by performing longitudinal stretching using the speed difference between rolls and transverse stretching using a tenter.
[0126] (Laminate) The laminate comprises at least one selected from the sheet and film of the present embodiment, and further comprises other components such as a printed layer and a resin film as necessary. The laminate can be obtained, for example, by laminating a film or sheet to one or both sides of at least one selected from the sheets and films of the present embodiment in order to improve mechanical strength, chemical resistance, etc. Specifically, the laminate can be obtained by thermally laminating a polystyrene-based inflation film to at least one of the front side and back side of the sheet or film, or by laminating an olefin-based film (CPP) using an adhesive. The adhesive used is not particularly limited, and may be, for example, the adhesive of the present embodiment or a known adhesive.
[0127] (Molded body) The molded article can be obtained by molding at least one selected from the sheet, film, and laminate of the present embodiment. The molded article can be obtained, for example, by thermoforming the sheet, film, or laminate of the present embodiment. Examples of the thermoforming method include hot plate contact heat molding, vacuum molding, vacuum pressure molding, and plug assist molding. In particular, indirect heat molding using an infrared heater as a heat source is preferably used. EXAMPLES
[0128] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0129] <Chemical structure evaluation> In the examples and comparative examples, the chemical structure of the resin was determined by nuclear magnetic resonance ( 13 The compound was identified using C-NMR under the following conditions. Measurement equipment: JEOL RESONANCE "JNM-ECM400S" Magnetic field strength: 100MHz Number of times: 1000 Solvent: Deuterated chloroform Paramagnetic relaxation reagent: Chromium(III) acetylacetate. Sample concentration: 200mg / 1.0mL
[0130] <Evaluation of average sequence length> <<Peak integral calculation>> Obtained 13 The C-NMR spectrum was subjected to waveform separation processing using JEOL Delta v5.3.1 software, and the triad peak integral value was calculated. <<Calculation of the average sequence length of quaternary polyester>> The average sequence length was calculated based on the formula shown below. L x-y=(I x-y-x ×2) / (I x-w-x +I z-y―x +I z-y-x +I x-y-z +I y-x-w )+1 L: average chain length I: Triad peak integral value x: A structural unit derived from 2-methyl-1,3-propanediol y: Adipic acid-derived building block z: A structural unit derived from 1,4 butanediol w: Succinic acid-derived building block
[0131] [Calculation of the average sequence length of copolyesters containing hydroxyalkanoic acid] The average sequence length was calculated based on the formula shown below. L h-h =1+2×(I s-h-h +I h-h-h ) / (I s-h-b +I h-h―b +I b-s-h +I h-s-h ) L: average chain length I: Triad peak integral value h: 6-hexanoate-derived building block s: 1,4-succinate-derived building block b: 1,4-butanoate-derived building block
[0132] <Evaluation of molecular weight> In the examples and comparative examples, the molecular weight of the resin was measured by gel permeation chromatography (GPC) under the following conditions. Measurement equipment: System controller Waters 600 Controller Liquid delivery pump Waters Model Code 60F RI (Differential Refractometer) Detector Waters 2414 Autosampler Waters 717plus Autosampler Data processing: Waters Empower3 Measurement conditions Measurement conditions: Column temperature 40℃ Eluent: Chloroform (CHCl3) Flow rate 1.0ml / min Standard: Polystyrene Column: Shodex GPC LF-G x 1 Shodex GPC LF-804 4 pieces Sample: 100 μl of a chloroform solution containing 0.4% by mass of resin solids filtered through a microfilter
[0133] <Oxidation evaluation> In the examples and comparative examples, the acid value of the resin was calculated according to the following procedure. Approximately 1 g of sample was weighed out and placed in a stoppered Erlenmeyer flask, and 20 mL of acetone was added to dissolve it. Phenolphthalein test solution was added as an indicator and the solution was left to stand for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a pale pink color, and the acid value was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (mL) F: Factor of 0.1N alcoholic potassium hydroxide solution
[0134] <Melting point measurement> Measurement equipment: Mettler DSC822 Measurement conditions: under nitrogen flow, temperature rise / fall rate 5℃ / min, measurement temperature range -60℃~180℃
[0135] <Evaluation of biodegradability> In the examples and comparative examples, the degree of biodegradation was calculated according to the following procedure, and the biodegradability was evaluated from the value of the degree of biodegradation.
[0136] <<Evaluation of seawater decomposition>> Inoculum source: Seawater collected from the coast of Akane Bay (near Akanehama, Narashino City, Chiba Prefecture) was used as the inoculum source. Biodegradability measurement method: Soda lime (carbon dioxide absorbent) and a pressure sensor (WTW, OxiTop-IDS (registered trademark)) were attached to a test bottle, and the BOD (biological oxygen demand) was measured under the conditions below to calculate the biodegradability. Culture temperature: 27℃, dark place Culture period: 28 days Calculation of biodegradability: The biodegradability of the resin samples of the Examples and Comparative Examples was calculated based on the following formula. Biodegradability (%)=(BOD0-BODB) / ThOD×100 BOD0: Biochemical oxygen demand of the sample (measured value: mg) BODB: Average biochemical oxygen demand in blank test (measured value: mg) ThOD: Theoretical oxygen demand required for complete oxidation of the sample (calculated value: mg) Evaluation criteria: A (best): Biodegradability is 50% or more B (Excellent): Biodegradability is between 40% and 50% C (Good): Biodegradability is 24% or more but less than 40% D (Acceptable): Biodegradability is between 15% and 24% (lower practical limit) E (unacceptable): Biodegradability is less than 15% (not suitable for practical use)
[0137] <<Evaluation of freshwater degradability>> Degradability was evaluated in the same manner as described in the evaluation of seawater degradability, except that the inoculum source was river water collected from the Inagawa River (near Momozono, Ikeda City, Hyogo Prefecture).
[0138] <<Evaluation of soil decomposition>> Degradability was evaluated in the same manner as described for the evaluation of seawater degradability, except that the inoculum source was soil collected from Oshiozuka Community Farm (near Oshiozuka, Sakura City, Chiba Prefecture).
[0139] <<Evaluation of compost decomposition>> The compost decomposition rate was measured using a method in accordance with JIS K6953-1:2011. Culture temperature: 58℃ Culture period: 28 days Evaluation criteria: A (best): Compost decomposition rate is 50% or more B (Excellent): Compost decomposition rate is between 40% and 50% C (Good): Compost decomposition rate is between 24% and 40% D (Acceptable): Compost decomposition rate is between 15% and 24% (lower practical limit) E (unacceptable): Compost decomposition rate is less than 15% (not suitable for practical use)
[0140] (Synthesis Example 1) <Synthesis of poly(2-methyl-1,3 propanediol / adipic acid) (P(2MPD / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 396 parts by mass of 2-methyl-1,3 propanediol (2MPD), 604 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(2MPD / AA) was obtained. The structure of P(2MPD / AA) is shown in formula (9).
[0141] [ka] Formula (9) (In formula (9), a represents a positive integer.)
[0142] The biodegradability evaluation results showed that the biodegradability was 63% in seawater, 65% in freshwater, and 78% in soil, and the compost decomposition rate was 83%. The average molecular weight was measured to find that the number average molecular weight Mn was 10,071 and the weight average molecular weight Mw was 31,524.
[0143] (Synthesis Example 2) <Synthesis of poly(1,4 butanediol / succinic acid) (P(BG / SA))> P(BG / SA) was obtained in the same manner as in Synthesis Example 1, except that 441 parts by mass of 1,4-butanediol (BG), 559 parts by mass of succinic acid (SA), and 0.2 parts by mass of titanium tetraisopropoxide (TIPT) were used as raw materials and the temperature of the reaction liquid was set to 220° C. The structure of P(BG / SA) is shown in formula (10).
[0144] [ka] Formula (10) (In formula (10), b represents a positive integer.)
[0145] The biodegradability evaluation results showed that the biodegradability was 3% in seawater, 3% in freshwater, and 10% in soil, and the compost decomposition rate was 13%. The average molecular weight was measured, and the number average molecular weight Mn was 12,254, and the weight average molecular weight Mw was 28,416.
[0146] (Synthesis Example 3) <Synthesis of poly(2-methyl-1,3 propanediol / sebacic acid) (P(2MPD / SebA))> As raw materials, 322 parts by mass of 2-methyl-1,3 propanediol (2MPD), 678 parts by mass of sebacic acid (SebA), and 0.2 parts by mass of titanium tetraisopropoxide (TIPT) were used, and P(2MPD / SebA) was obtained in the same manner as in Synthesis Example 1. The structure of P(2MPD / SebA) is shown in formula (11).
[0147] [ka] Formula (11) (In formula (11), c represents a positive integer.)
[0148] The biodegradability evaluation results showed that the biodegradability was 65% in seawater, 65% in freshwater, and 74% in soil, and the compost decomposition rate was 83%. The average molecular weight was measured to find that the number average molecular weight Mn was 19,587 and the weight average molecular weight Mw was 63,356.
[0149] (Synthesis Example 4) <Synthesis of poly(3-methyl-1,5-propanediol / adipic acid) (P(3MPD / AA))> As raw materials, 458 parts by mass of 3-methyl-1,5-propanediol (3MPD), 542 parts by mass of adipic acid (AA), and 0.2 parts by mass of titanium tetraisopropoxide (TIPT) were used, and P(3MPD / AA) was obtained in the same manner as in Synthesis Example 1. The structure of P(3MPD / AA) is shown in formula (12).
[0150] [ka] Formula (12) (In formula (12), d represents a positive integer.)
[0151] The biodegradability evaluation results showed that the biodegradability was 63% in seawater, 64% in freshwater, and 78% in soil, and the compost decomposition rate was 85%. The average molecular weight was measured to find that the number average molecular weight Mn was 13,880 and the weight average molecular weight Mw was 42,954.
[0152] (Synthesis Example 5) <Synthesis of poly(1,4 butanediol / adipic acid / terephthalic acid) (P(BG / AA / tPA))> P(BG / AA / tPA) was obtained in the same manner as in Synthesis Example 1, except that the raw materials used were 398 parts by mass of 1,4-butanediol (BG), 292 parts by mass of adipic acid (AA), 332 parts by mass of terephthalic acid (tPA), and 0.2 parts by mass of titanium tetraisopropoxide (TIPT), and the temperature of the reaction liquid was set to 220° C. The structure of P(BG / AA / tPA) is shown in formula (13).
[0153] [ka] Formula (13) (In formula (13), e and f each independently represent a positive integer.)
[0154] The biodegradability evaluation results showed that the biodegradability was 3% in seawater, 3% in freshwater, and 8% in soil, and the compost decomposition rate was 10%. The average molecular weight was measured, and the number average molecular weight Mn was 26,445, and the weight average molecular weight Mw was 81,430.
[0155] (Synthesis Example 6) <Synthesis of poly(ethylene glycol / adipic acid) (P(EG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, rectification tube, and water separator, 306 parts by mass of ethylene glycol (EG), 694 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 190°C and the vapor temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less, and P(EG / AA) was obtained. The structure of P(EG / AA) is shown in formula (14).
[0156] [ka] Formula (14) (In formula (14), a represents a positive integer.)
[0157] The biodegradability evaluation showed that the biodegradability was 50% in seawater, 52% in freshwater, and 55% in soil, and 65% in compost. The average molecular weight was measured to find that the number average molecular weight Mn was 5,568 and the weight average molecular weight Mw was 14,619.
[0158] (Synthesis Example 7) <Synthesis of poly(diethylene glycol / adipic acid) (P(DEG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 431 parts by mass of diethylene ethylene glycol (DEG), 569 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(DEG / AA) was obtained. The structure of P(DEG / AA) is shown in formula (15).
[0159] [ka] Formula (15) (In formula (15), a represents a positive integer.)
[0160] The biodegradability evaluation showed that the biodegradability was 63% in seawater, 65% in freshwater, and 70% in soil, and the compost decomposition rate was 78%. The average molecular weight was measured, and the number average molecular weight Mn was 14,200 and the weight average molecular weight Mw was 102,600.
[0161] (Synthesis Example 8) <Synthesis of poly(1,2-propanediol / adipic acid) (P(1,2PG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 351 parts by mass of 1,2-propanediol (1,2PG), 649 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(1,2PG / AA) was obtained. The structure of P(1,2PG / AA) is shown in formula (16).
[0162] [ka] Formula (16) (In formula (16), a represents a positive integer.)
[0163] The biodegradability evaluation showed that the biodegradability was 71% in seawater, 67% in freshwater, and 75% in soil, and 81% in compost. The average molecular weight was measured to find that the number average molecular weight Mn was 6,870 and the weight average molecular weight Mw was 14,070.
[0164] (Synthesis Example 9) <Synthesis of poly(1,3-butanediol / adipic acid) (P(1,3BG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 391 parts by mass of 1,3-butanediol (1,3BG), 609 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 190°C and the vapor temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less, yielding P(1,3BG / AA). The structure of P(1,3BG / AA) is shown in formula (17).
[0165] [ka] Formula (17) (In formula (17), a represents a positive integer.)
[0166] The biodegradability evaluation showed that the biodegradability was 60% in seawater, 59% in freshwater, and 63% in soil, and 78% in compost. The average molecular weight was measured to find that the number average molecular weight Mn was 14,700 and the weight average molecular weight Mw was 92,000.
[0167] (Synthesis Example 10) <Synthesis of poly(1,3-propanediol / adipic acid) (P(1,3PG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 351 parts by mass of 1,3-propanediol (1,3PG), 649 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 200°C and the vapor temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less, yielding P(1,3PG / AA). The structure of P(1,3PG / AA) is shown in formula (18).
[0168] [ka] Formula (18) (In formula (18), a represents a positive integer.)
[0169] The biodegradability evaluation showed that the biodegradability was 47% in seawater, 49% in freshwater, and 55% in soil, and the compost decomposition rate was 68%. The average molecular weight was measured, and the number average molecular weight Mn was 5,540, and the weight average molecular weight Mw was 24,500.
[0170] (Synthesis Example 11) <Synthesis of poly(1,4-butanediol / adipic acid) (P(1,4BG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 391 parts by mass of 1,4-butanediol (1,4BG), 609 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C. The reaction was terminated when the acid value of the reaction liquid became 2 mgKOH / g or less, yielding P(1,4BG / AA). The structure of P(1,4BG / AA) is shown in formula (19).
[0171] [ka] Formula (19) (In formula (19), a represents a positive integer.)
[0172] The biodegradability evaluation showed that the biodegradability was 61% in seawater, 62% in freshwater, and 68% in soil, and 78% in compost. The average molecular weight was measured and found to be number-average molecular weight Mn of 27,200 and weight-average molecular weight Mw of 132,000.
[0173] (Synthesis Example 12) <Synthesis of poly(1,5-pentanediol / adipic acid) (P(1,5PG / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 426 parts by mass of 1,5-pentanediol (1,5PG), 574 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(1,5PG / AA) was obtained. The structure of P(1,5PG / AA) is shown in formula (20).
[0174] [ka] Formula (20) (In formula (20), a represents a positive integer.)
[0175] The biodegradability evaluation showed that the biodegradability was 63% in seawater, 65% in freshwater, and 67% in soil, and 76% in compost. The average molecular weight was measured and found to be number-average molecular weight Mn of 6,210 and weight-average molecular weight Mw of 26,900.
[0176] (Synthesis Example 13) <Synthesis of poly(1,6-hexanediol / adipic acid) (P(1,6HD / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, distillation tube, and water separator, 458 parts by mass of 1,6-hexanediol (1,6HD), 542 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(1,6HD / AA) was obtained. The structure of P(1,6HD / AA) is shown in formula (21).
[0177] [ka] Formula (21) (In formula (21), a represents a positive integer.)
[0178] The biodegradability evaluation showed that the biodegradability was 55% in seawater, 54% in freshwater, and 62% in soil, and the compost decomposition rate was 68%. The average molecular weight was measured and found to be number average molecular weight Mn9634 and weight average molecular weight Mw30394.
[0179] (Synthesis Example 14) <Synthesis of poly(1,9-nonanediol / adipic acid) (P(1,9ND / AA))> In a polyester reaction vessel equipped with a stirrer, nitrogen gas inlet tube, rectification tube, and water separator, 535 parts by mass of 1,9-nonanediol (1,9ND), 465 parts by mass of adipic acid (AA), and 0.1 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the esterification reaction was carried out under a nitrogen stream while maintaining the liquid temperature of the reaction liquid at 220°C and the vapor temperature at 98°C. When the acid value of the reaction liquid became 2 mgKOH / g or less, the reaction was terminated, and P(1,9ND / AA) was obtained. The structure of P(1,9ND / AA) is shown in formula (22).
[0180] [ka] Formula (22) (In formula (22), a represents a positive integer.)
[0181] The biodegradability evaluation showed that the biodegradability was 58% in seawater, 57% in freshwater, and 65% in soil, and 75% in compost. The average molecular weight was measured and found to be number-average molecular weight Mn of 4,410 and weight-average molecular weight Mw of 28,900.
[0182] Example 1 A glass vessel equipped with a stirrer and a nitrogen gas inlet tube was charged with 57 parts by mass of P(2MPD / AA) obtained in Synthesis Example 1, 443 parts by mass of P(BG / SA) obtained in Synthesis Example 2, and 0.05 parts by mass of titanium tetraisopropoxide (TIPT), and the vessel was maintained at 200°C for 3 hours under a nitrogen stream to obtain a copolyester resin containing 2MPD / AA and BG / SA as structural units. The structure of the obtained copolyester resin is shown in formula (A-1).
[0183] [ka] Formula (A-1) (In formula (A-1), o, p, and q each independently represent a positive integer.)
[0184] Evaluation of the average sequence length showed that the 2MPD / AA average sequence length was 6.9. The biodegradability evaluation results showed that the decomposition rate in seawater was 16% and in compost was 62%. The results of the biodegradability evaluation are shown in Table 1 below (Table 1A, Table 1B). Hereinafter, Table 1A and Table 1B will be collectively referred to as Table 1.
[0185] (Examples 2 to 6) The same procedure as in Example 1 was carried out except that the amounts of P(2MPD / AA) and P(BG / SA) and the maintenance time as the reaction time were changed to the values shown in Table 1, to obtain a copolyester resin.
[0186] Example 7 A copolyester resin was obtained in the same manner as in Example 1, except that 305 parts by mass of P(BG / SA) obtained in Synthesis Example 2, 195 parts by mass of P(2MPD / SebA) obtained in Synthesis Example 3, and 0.05 parts by mass of titanium tetraisopropoxide (TIPT) were charged as raw materials and the maintenance time, which is the reaction time, was changed to the value shown in Table 1. The structure of the obtained copolyester resin is shown in formula (A-2).
[0187] [ka] Formula (A-2) (In formula (A-2), o, p, and q each independently represent a positive integer.)
[0188] Example 8 A copolyester resin was obtained in the same manner as in Example 1, except that 319 parts by mass of P(BG / SA) obtained in Synthesis Example 2, 181 parts by mass of P(3MPD / AA) obtained in Synthesis Example 4, and 0.05 parts by mass of titanium tetraisopropoxide (TIPT) were charged as raw materials and the maintenance time, which is the reaction time, was changed to the value shown in Table 1. The structure of the obtained copolyester resin is shown in formula (A-3).
[0189] [ka] Formula (A-3) (In formula (A-3), o, p, and q each independently represent a positive integer.)
[0190] Example 9 A copolyester resin was obtained in the same manner as in Example 1, except that 104 parts by mass of P(2MPD / AA) obtained in Synthesis Example 1, 390 parts by mass of P(BG / AA / tPA) obtained in Synthesis Example 5, and 0.05 parts by mass of titanium tetraisopropoxide (TIPT) were charged as raw materials and the maintenance time, which is the reaction time, was changed to the value shown in Table 1. The structure of the obtained copolyester resin is shown in formula (A-4).
[0191] [ka] Formula (A-4) (In formula (A-4), o, p, q and r each independently represent a positive integer.)
[0192] Example 10 500 parts by mass of P(2MPD / AA / BG / SA) obtained in Example 5 was placed in a four-neck flask equipped with a thermometer, a stirrer, a nitrogen gas inlet, and a reflux condenser, and dissolved in 300 parts by mass of ethyl acetate to obtain an ethyl acetate solution of polyester polyol. 0.1 parts by mass of dibutyltin dilaurate (DBTDL) and 13 parts by mass of isophorone diisocyanate (IPDI) were added to the solution, and the reaction was carried out while maintaining the temperature at 70 to 80°C under a nitrogen stream. The reaction was terminated when the isocyanate weight ratio became less than 0.05% by mass, and a polyester urethane polyol solution was obtained.
[0193] Example 11 The same procedure as in Example 10 was carried out except that the raw material was changed to 10 parts by mass of hexamethylene diisocyanate (HDI), to obtain a polyester urethane polyol solution.
[0194] Example 12 The same procedure as in Example 10 was carried out except that the raw material was changed to 15 parts by mass of diphenylmethane diisocyanate (MDI), to obtain a polyester urethane polyol solution.
[0195] Comparative Example 1 P(BG / SA) obtained in Synthesis Example 2 was used.
[0196] The reaction conditions and evaluation results of Examples 1 to 9 and Comparative Example 1 are summarized in Table 1. The reaction conditions and evaluation results of Examples 10 to 12 are summarized in Table 2.
[0197] [Table 1A]
[0198] [Table 1B]
[0199]
Table 2
[0200] (Synthesis Example 15) <Synthesis of Poly(caprolactone) (PCL)> Into a reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a rectification tube, a water separator, etc., 487 parts by mass of ε-caprolactone (εCL) and 5 parts by mass of methanesulfonic acid were charged, and a ring-opening polymerization reaction was allowed to proceed for 5 hours while maintaining the liquid temperature of the reaction solution at 100 °C under a nitrogen stream to obtain poly(caprolactone) (PCL). The structure of PCL is shown in Formula (23).
[0201]
Chemical formula
[0202] Using the method for measuring the average molecular weight described above, the average molecular weight was measured. The number average molecular weight Mn was 14,630, and the weight average molecular weight Mw was 23,882. The 1 1H-NMR measurement method was used to 1 measure the 1H-NMR spectrum. The results are as follows. 1 1H-NMR δ(CDCl3): 1.30 - 1.38 (m, 2H), 1.57 - 1.64 (m, 4H), 2.26 (t, 2H), 4.01 (t, 2H)
[0203] As a result of the evaluation of biodegradability, the biodegradation degrees were 78% in seawater, 77% in fresh water, and 79% in soil, respectively, and the compost decomposition rate was 83%.
[0204] <Capa6400 (Ingevity, product PCL)> As a result of the evaluation of the average molecular weight, the number-average molecular weight Mn was 24,400 and the weight-average molecular weight Mw was 87,757. As a result of the evaluation of biodegradability, the biodegradation degrees were 76% in seawater, 77% in fresh water, and 78% in soil, respectively, and the compost decomposition rate was 81%.
[0205] <BioPBS (Mitsubishi Chemical, product P(BG / SA))> As a result of the evaluation of the average molecular weight, the number-average molecular weight Mn was 59,499 and the weight-average molecular weight Mw was 171,333. As a result of the evaluation of biodegradability, the biodegradation degrees were 2% in seawater, 1% in fresh water, and 6% in soil, respectively, and the compost decomposition rate was 12%.
[0206] <Ecoflex (BASF, product P(BG / AA / tPA))> As a result of the evaluation of the average molecular weight, the number-average molecular weight Mn was 26,445 and the weight-average molecular weight Mw was 81,430. As a result of the evaluation of biodegradability, the biodegradation degrees were 1% in seawater, 1% in fresh water, and 6% in soil, respectively, and the compost decomposition rate was 10%.
[0207] (Example 13) 5.4 parts by mass of Capa6400 (Ingevity, product PCL), 400 parts by mass of BioPBS (Mitsubishi Chemical, product P(BG / SA)), and 0.08 parts by mass of titanium tetraisopropoxide (TIPT) were charged into a glass container equipped with a stirrer and a nitrogen gas introduction tube, and the container was maintained at 200 °C under reduced pressure for 6 hours to obtain a copolyester containing PCL and BG / SA as constituent units. The structure of the obtained copolyester is shown in formula (B-1).
[0208]
Chemical formula
[0209] Using the method described above, the average chain length of the structural unit (6HH-U) derived from 6-hydroxyhexanoic acid (6HH) constituting PCL was calculated as the average chain length of the biodegradable block (X). In addition, biodegradability was evaluated and the average molecular weight was measured. The results are shown in Table 3 (Table 3A, Table 3B). Hereinafter, Table 3A and Table 3B will be collectively referred to as Table 3.
[0210] Example 14 In a glass vessel equipped with a stirrer and a nitrogen gas inlet tube, 11 parts by mass of PCL obtained in Synthesis Example 15, 400 parts by mass of P(BG / SA) obtained in Synthesis Example 2, and 0.08 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the vessel temperature was maintained at 200°C for 3 hours under a nitrogen stream to obtain a copolyester containing PCL and BG / SA as structural units. The structure of the obtained copolyester is shown in formula (B-2).
[0211] [ka] Formula (B-2) (In formula (B-2), o, p, and q each independently represent a positive integer.)
[0212] Using the same method as in Example 13, the average sequence length was calculated, the biodegradability was evaluated, and the average molecular weight was measured. The results are shown in Table 3.
[0213] (Examples 15, 17, 18, 20 to 22) The same procedure as in Example 14 was carried out except that the blending amounts of PCL and P(BG / SA) and the maintenance time as the reaction time were changed to the values shown in Table 3, to obtain a copolyester. The same evaluation as in Example 13 was carried out, and the results are shown in Table 3.
[0214] (Examples 16, 19, and 23) The same procedure as in Example 13 was carried out except that the blending amounts of PCL and P(BG / SA) and the maintenance time as the reaction time were changed to the values shown in Table 3, to obtain a copolyester. The same evaluation as in Example 13 was carried out, and the results are shown in Table 3.
[0215] Example 24 In a glass vessel equipped with a stirrer and a nitrogen gas inlet tube, 197 parts by mass of Capa6400 (Ingevity, product PCL), 300 parts by mass of BioPBS (Mitsubishi Chemical, product P(BG / SA)), and 0.09 parts by mass of titanium tetraisopropoxide (TIPT) were charged, and the vessel temperature was maintained at 200°C for 5 hours under a nitrogen stream to obtain a copolyester containing PCL and BG / SA as structural units. The structure of the obtained copolyester is shown in formula (B-3).
[0216] [ka] Formula (B-3) (In formula (B-3), o, p, and q each independently represent a positive integer.)
[0217] The same evaluation as in Example 13 was carried out, and the results are shown in Table 3.
[0218] (Example 25) A copolyester was obtained using 52 parts by mass of Capa6400 (Ingevity, product PCL), 351 parts by mass of Ecoflex (BASF, product P(BG / AA / tPA)), and 0.08 parts by mass of titanium tetraisopropoxide (TIPT) as raw materials in the same manner as in Example 13. The structure of the obtained copolyester is shown in formula (B-4).
[0219] [ka] Formula (B-4) (In formula (B-4), o, p, q and r each independently represent a positive integer.)
[0220] The same evaluation as in Example 13 was carried out, and the results are shown in Table 3.
[0221] [Table 3A]
[0222] [Table 3B] From the above examples, it was confirmed that the copolyester resin of the present invention is excellent in thermoformability and biodegradability, particularly in biodegradability.
Claims
1. A copolyester resin comprising a biodegradable block (X) which is a structural unit exhibiting biodegradability and a non-biodegradable block (Y) which is a structural unit having non-biodegradability, The biodegradable block (X) is derived from a structure in which a hydroxyalkanoic acid or a dibasic acid (I-a) is bound to a glycol (I-b), and is a biodegradable block (X) derived from a polymer (x) containing a biodegradable structural unit, The non-biodegradable block (Y) is derived from a polymer (y) containing a non-biodegradable structural unit, the non-biodegradable structural unit in the polymer (y) is derived from butylene succinate, The biodegradable block (X), which is a structural unit exhibiting biodegradability, contains a unit (A) and a unit (B), and the unit (A) and the unit (B) are any one of the following (i) to (iii): Copolyester resin. (i) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3-propanediol, adipic acid, and 2-methyl-1,3-propanediol are bonded together," and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, adipic acid, and 1,4-butanediol are bonded together," or (ii) The unit (A) is a triad unit derived from a "structure in which 2-methyl-1,3-propanediol, sebacic acid, and 2-methyl-1,3-propanediol are bonded" and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, sebacic acid, and 1,4-butanediol are bonded", or (iii) The unit (A) is a triad unit derived from a "structure in which 3-methyl-1,5-pentanediol, adipic acid, and 3-methyl-1,5-pentanediol are bonded together," and the unit (B) is a triad unit derived from a "structure in which 1,4-butanediol, adipic acid, and 1,4-butanediol are bonded together."
2. 2. The copolyester resin according to claim 1, wherein a molar ratio (X / Y) of the biodegradable block (X) to the non-biodegradable block (Y) is 1 / 99 to 95 / 5.
3. 2. The copolyester resin according to claim 1, wherein the average sequence length of the biodegradable block (X) is greater than 1.
2.
4. The non-biodegradable structural unit in the polymer (y) is 2. The copolyester resin according to claim 1, wherein the structural unit is derived from a structure in which 1,4-butanediol and succinic acid are bonded together.
5. 2. The copolyester resin of claim 1, wherein the copolyester resin has a melting point (Tm) of 65°C or higher.
6. The copolyester resin according to claim 1 , which exhibits biodegradability in a seawater environment, a freshwater environment, a soil environment, and a compost environment.
7. A method for producing the copolyester resin according to any one of claims 1 to 6, which comprises a combination of a biodegradable block (X) and a non-biodegradable block (Y), comprising the steps of: The biodegradable block (X) is a block derived from a polymer (x) containing a biodegradable structural unit, The non-biodegradable block (Y) is a block derived from a polymer (y) containing a non-biodegradable structural unit, a step of subjecting the polymer (x) and the polymer (y) to a transesterification reaction to obtain a block copolymer containing the biodegradable block (X) and the non-biodegradable block (Y); A method for producing a copolyester resin comprising the steps of:
8. A resin composition comprising the copolyester resin according to any one of claims 1 to 6.
9. A sheet or film comprising the resin composition according to claim 8.
Citation Information
Patent Citations
Biodegradable branched aromatic polyester-aliphatic polyester multi-block polymer
CN102344556A
Biodegradable branched aliphatic polyester multi-block copolymer and preparation method thereof
CN102516555A
Production of biodegradable polyester copolymer
JP1995157553A
Polyester block copolymer
JP1997143255A
Polyester polymer composition
JP1999323107A
Cited By
Copolyester resin and method for producing the same
JP2025020252A
